Seed, fertilizer, and agricultural extension in Ethiopia: Summary of ESSP working paper 20 - Spielman, David J.; Mekonnen, Dawit Kelemework; Alemu, Dawit (International Food Policy Research Institute, 2012)
Decisionmakers in Ethiopia have pursued a range of policies and investments to boost agricultural production and productivity. An important tool has been to increase the availability of improved seed, chemical fertilizers, and extension services for small-scale, resource-poor farmers. While there is some evidence to suggest that the process has led to improvements in both agricultural output and yields, there is an urgent need for more substantial progress. A rethinking of approaches is required, one that reallocates the roles of the public and private sectors in the agricultural input sector.